PREVALENCE OF SEXUAL HARASSMENT AMONG WOMEN AGRICULTURAL LABORERS AND PERCEIVED IMPACTS ON THEIR PHYSICAL & MENTAL HEALTH - Naveed Farah, Saima Afzal, Izhar Ahmad Khan (Pakistan Journal of Educational Research, 2022)
Large number of women is working as laborers in agricultural sector of Pakistan particularly in cotton picking, wheat harvesting, rice transplanting, and dairy sector. Gender based Violence and sexual harassment is fairly observable and reported in the formal sector of the urban areas but a research gap exists to study sexual harassment in informal sector, and particularly in agriculture sector. Present study is intended to understand the patterns and types of sexual harassment of woman laborers in agriculture sector. A sample of 250 women agricultural laborer/workers from five districts of Punjab province were selected for a face to face survey to explore the patterns of sexual harassment and its perceived impact for their health and the stigma attached to report such incidences. The views of male counterparts were obtained through key informant interviews of agricultural contractors and landlords. The results revealed that majority of the respondents faced gender based discrimination (50 %), low wages as compared to men (64 %), lack of respect (45.2 %) and negative attitudes of male workers (44 %). The data regarding verbal harassment indicated that such incidences are on the higher side (38.4 %) as compared to non-verbal (28.8 %) and physicaal (9.6 %) types of sexual harassment. The woman laborers also suffered different physical and psychological consequences of sexual harassment like; sleeping problem, depression, anxiety and isolation. However, the trend of not lodging the complaints by the victims was clearly evident i.e. 91.6 % representing the stigma and fear of disgrace associated with sexual harassment in the rural communities of Pakistan. Strong advocacy campaigns by academia and Non-governmental agencies to sensitize the rural communities are seriously required coupled with extending the purview of labor laws and harassment act of Pakistan to informal workers by policy makers.